The impact of resource management practices on the performance of micro and small enterprises in Werabe Town, Ethiopia - Refera, Matewos Kebede; Habib, Redela Seman; Lemma, Habtamu Regassa; Seman, Abdilkerim Asrar; Antonios, Endalew Adamu (Frontiers in Sustainability, 2025)
IntroductionEfficient resource management is essential for enhancing organizational performance; however, its implementation in micro and small enterprises (MSEs) has received limited academic attention. Taking into account these obvious reasons, this study aims to investigate the influence of resource management practices on the performance of micro and small enterprises in Werabe Town, Ethiopia.MethodsWe distributed a structured questionnaire to 265 randomly selected small business operators. Both descriptive and inferential statistical methods, including correlation and regression analysis were used to analyse the collected data.ResultsThe findings indicate low overall MSE performance, driven by inadequate financial, human resource, material, and information management practices. Based on regression analysis, these four factors explain 64.3% of the variations in performance, showing that they have a positive and statistically significant effect.ConclusionTherefore, improving financial planning, cash flow, and working capital management is crucial for maintaining efficient financial operations. However, financial efficiency alone is not enough; a formal HR planning process, a well-defined job description, carrying out a recruiting and selection, and establishing a pay system are equally crucial. Additionally, streamlining material requirement planning, procurement processes, and inventory control systems ensures resource availability and operational efficiency. Furthermore, pre-made and streamlined information management software is appropriate to improve the flow of information for better decision-making across financial, human, and material resources.